Ranibizumab treatment patterns in prior ranibizumab-treated neovascular age-related macular degeneration patients: Real-world outcomes from the LUMINOUS study - Holz, Frank G. (PLoS One, 2020)
PURPOSE: To evaluate the effectiveness, safety, and treatment patterns of ranibizumab 0.5 mg in prior ranibizumab-treated patients with neovascular age-related macular degeneration (nAMD) enrolled in the LUMINOUS(™) study. PATIENTS AND METHODS: LUMINOUS, a 5-year, prospective, multicenter, observational study, recruited 30,138 adult patients (treatment-naïve or prior ranibizumab-treated or other ocular treatments) across all approved indications for ranibizumab. Patients were treated as per local ranibizumab label of participating countries. Here we report the mean change in visual acuity (VA) at Year 1, treatment exposure, overall incidence of ocular, non-ocular adverse events (AEs) and serious AEs (SAEs) in prior ranibizumab-treated nAMD patients (n = 16,167). RESULTS: At baseline, the mean (standard deviation [SD]) age of patients was 78.4 (9.0) years, 59.0% were female, and 80.0% were Caucasian. At Year 1 (n = 10,168), the mean (SD) VA change was −1.6 (12.6) letters (baseline VA: 58.3 [19.0] letters) with a mean (SD) of 4.7 (3.1) ranibizumab injections. Stratified by duration of prior ranibizumab treatment of <1 (n = 4,112), 1 to <2 (n = 2,095), 2 to <3 (n = 1,506), 3 to <4 (n = 1,123), 4 to <5 (n = 689), and ≥5 (n = 256) years, the mean (SD) VA change at Year 1 were −1.2 (13.5), −2.0 (12.3), −2.0 (11.3), −1.9 (11.8), −2.5 (10.9), and 0.0 (11.2) letters, respectively. Mean (SD) VA change in patients who received ≤6 and >6 injections over 1 year was −1.8 (13.8) and +0.5 (12.5) letters, respectively. The rate of ocular/non-ocular AEs and SAEs across all prior ranibizumab-treated patients over 5 years were 13.29%/23.02% and 0.84%/13.66%, respectively. CONCLUSIONS: Overall, regardless of the prior ranibizumab-treatment duration, VA was maintained in these patients at Year 1, and those receiving ≥6 injections showed a trend towards gaining letters. There were no new safety signals. These results may help inform routine clinical practice to appropriately treat nAMD patients with ranibizumab to achieve optimal visual outcomes.